O Conto da Aia à luz da recepção virtual: literatura e série televisiva sob a perspectiva de receptores contemporâneos - BORGES, Jaynne Silva de Sousa (2023)
This dissertation has as its object of study the literary work The Handmaid's Tale (1985), by Margaret Atwood, and the 2017 streaming series of the same name, created by Bruce Miller. The theme focuses on studying the two productions in the light of the Aesthetics of Virtual Reception theory; therefore, the guiding question of this research is: how does the reception process of the book and the series The Handmaid’s Tale take place? Thus, the general objective of this work is to analyze this phenomenon, based on a study of the consumption and reception of the audiences of both works, including also the construction and presentation of each one, and the strategies and intentions of their authors. The methodology used is bibliographical, with qualitative analysis procedures. The theoretical referential is composed by researchers such as Naiara Araújo (2018), Carlos Berriel (2005), Leomir Hilário (2013), Gregory Claeys (2010, 2017) and Jessica Langer (2010), in the initial chapter, which deals with the dystopian fiction subgenre and the main characteristics that compose it. For the second chapter, there is the canonical contribution of Hans Robert Jauss (2011a, 2011b) and Wolfgang Iser (2011), for discussions on Reception Aesthetics, in addition to relevant research by Vicenzo Suzca (2021), Fellip Andrade (2020), and Baihui Chen (2021), regarding television series and their interactive potential with the audience. Many other researchers contribute in this work, made up of established theories and new perspectives on the issues addressed here. The results point out that audiences use both works specially to reflect on gender and other minority issues, as well as on the political landscape, themes that are directly related. For this reason, the story of The Handmaid's Tale – whether the book or the series – serves as a symbol of in-person and virtual manifestations in the struggle for social rights.